Construção de saberes sobre o lazer nas trajetórias de formadores/as do Programa Esporte e Lazer da Cidade (PELC) - André Henrique Chabaribery Capi (2016)
The PELC is a program coordinated by Secretaria Nacional de Esporte, Educação, Lazer e Inclusão Social (SNELIS), from Ministério do Esporte (ME) that develops its implementation actions of centers of recreational sports and leisure in agreements signed with regional and local governments, public universities and federal institutions in order to democratize and universalize access to practices and knowledge of leisure and sport. The axis of the professional training is a main action to the development of this social program and it is developed by Ministério do Esporte in partnership with the Universidade Federal de Minas Gerais. This action has the participation of 20 trainers selected by public bidding and develops training actions in PELC covenants. The analysis about the trajectory and the formative processes of the professionals who act as trainers for Programa Esporte e Lazer da Cidade was a way to understand how this construction of knowledge about leisure of these professionals happens considering the different dimensions of life that acts as a reference for these subject. The objective of the research was to analyze the professional career of the group of trainers; understand how personal knowledge and training (considering the relationship with the spaces, people, institutions and experiences) were built and articulated with their career in acting as a trainer of PELC and examine whether the leisure experiences of trainers influence and / or were appropriate as a knowledge about the leisure and the possible relationship with the qualification in professional training to act in the area. For research I combined procedures of bibliographic research, documentary and of field. In documentary research I consulted and analyzed the official documents and technical / teaching the PELC and Lattes system of sixteen trainers who participated in the survey. In field research I used the techniques of semi-structured interviews and focus groups (GF) that I conducted through Hangout On Hair. I used the content analysis to grasp the information captured in the procedures of field and documentary research. Data analysis allowed me to identify the trainers experienced in their career, from their childhood until that one that produces and experiences in various spheres today, they reflected in their way of being, living, acting and conduct. They reveal in these spheres, which entrenched by subjectivities, senses and meanings that marked themselves and allowed them to establish the relationship between knowledge and power us and with the groups which they live and act. I understand that this knowledge are related to play, sports, leisure, public policy, policy, training, cultural training, strategies, methodologies. Knowledge that should always be contextualized with the reality, considering the daily life of individuals who are part of their intervention, this way allows the reinvention of individuals and the action itself. The trainers recognize that to act in the field of leisure there is a need for cultural training, manifested through activities linked the various languages and cultural events (art, music, dance, theater, Movie Theater, trips). In this way leisure experiences can connect the pedagogical interventions of leisure professional, making the culture a sphere of life of individuals causing the interrogation and the questioning of truths of knowledge, curriculum and education produced in their life and in the society